The Implementation of Hope Family Program (PKH) in Poverty Prevention Effort in Kluwut Village Bulakamba District Brebes Regency - Simanjuntak, Agnes Pradina; Rusdarti, Rusdarti; Prasetyo, P. Eko (Universitas Negeri Semarang, 2019)
PKH (Hope Family Program) is a social assistance program that provides conditional cash assistance to very poor families (KSM) and in return, the KSM is required to fulfill the relevant requirements in an effort to improve the quality of human resources, which is education and health. The most PKH in Brebes Regency is in Kluwut village, Bulakamba district. The life of coastal communities and fishermen, with the potential of adequate natural resources, is often not commensurate with their income and decent living. This is one of the factors that caused many residents of Kluwut village to become recipients of PKH assistance. The research objectives are (1). Describe the characteristics of PKH participants in Kluwut village, Bulakamba district, Brebes Regency. (2). Analyzing PKH Implementation in Kluwut village. (3). Analyze the mechanism of PKH distribution in Kluwut village. (4). Analyze the obstacles faced in implementing the PKH in Kluwut village. (5). Analyze the solutions to overcome the obstacles of the PKH implementation in Kluwut village. This type of research is a qualitative descriptive. The data collection method in this study was questionnaire and interview techniques. The questionnaire took a sample of 30 PKH participants and interviewed 14 informants relating to this study. The results of the study showed that the implementation of PKH in Kluwut village has gone well and is able to improve the standard of living of PKH participants through access to education and health services.